Antibacterial action of a heat-stable form of L-amino acid oxidase isolated from King Cobra (Ophiophagus hannah) venom - Lee, M.L.; Tan, N.H.; Fung, S.Y.; Sekaran, S.D. (2011)
The major l-amino acid oxidase (LAAO, EC 1.4.3.2) of king cobra (Ophiophagus hannah) venom is known to be an unusual form of snake venom LAAO as it possesses unique structural features and unusual thermal stability. The antibacterial effects of king cobra venom LAAO were tested against several strains of clinical isolates including Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli using broth microdilution assay. For comparison, the antibacterial effects of several antibiotics (cefotaxime, kanamycin, tetracycline, vancomycin and penicillin) were also examined using the same conditions. King cobra venom LAAO was very effective in inhibiting the two Gram-positive bacteria (S. aureus and S. epidermidis) tested, with minimum inhibitory concentration (MIC) of 0.78 Î¼g/mL (0.006 Î¼M) and 1.56 Î¼g/mL (0.012 Î¼M) against S. aureus and S. epidermidis, respectively. The MICs are comparable to the MICs of the antibiotics tested, on a weight basis. However, the LAAO was only moderately effective against three Gram-negative bacteria tested (P. aeruginosa, K. pneumoniae and E. coli), with MIC ranges from 25 to 50 Î¼g/mL (0.2â0.4 Î¼M). Catalase at the concentration of 1 mg/mL abolished the antibacterial effect of LAAO, indicating that the antibacterial effect of the enzyme involves generation of hydrogen peroxide. Binding studies indicated that king cobra venom LAAO binds strongly to the Gram-positive S. aureus and S. epidermidis, but less strongly to the Gram-negative E. coli and P. aeruginosa, indicating that specific binding to bacteria is important for the potent antibacterial activity of the enzyme.